Novel angiotensin-converting enzyme inhibitory peptides derived from Trichiurus lepturus myosin: Molecular docking and surface plasmon resonance study. (August 2019) - Fu, Weiqing; Chen, Chuanjie; Zeng, Hongliang; Lin, Jiaxin; Zhang, Yi; Hu, Jiamiao; Zheng, Baodong
Abstract: In this study, two angiotensin-converting enzyme inhibitory peptides (ACEIPs) were isolated from Trichiurus lepturus myosin by trypsin hydrolysis for 5 h, ultrafiltration, with membrane of 3 kDa molecular weight cut-off and three-stage reversed-phase high-performance liquid chromatography (RP-HPLC). The amino acid sequences of these two peptides were determined as Ala–Asn–Ser–Glu–Val–Ala–Gln–Trp–Arg (ANSEVAQWR) and Glu–Ala–Leu–Val–Ser–Gln–Leu–Thr–Arg (EALVSQLTR), which possess the IC50 values of 89.58 and 91.48 μM, respectively. Moreover, the molecular docking suggested peptide ANSEVAQWR interacts with angiotensin-converting enzyme (ACE) via 11 hydrogen bonds and binds at both S1/S2 pockets; while peptide EALVSQLTR forms 9 hydrogen bonds and binds at S2 pocket only. Furthermore, the interaction between two peptides with ACE was determined by surface plasmon resonance (SPR), which revealed the dissociation rate (KD value) of peptide of ANSEVAQWR and EALVSQLTR for ACE were 1.4 × 10 −7 and 2.06 × 10 −4  M, respectively. Taken together, these results indicated that the two peptides isolated from T. lepturus myosin exhibited significant ACE inhibitory activity, and the interactions with active site pockets and binding strength of peptides determine their ACE inhibitory activity. Highlights: Two new ACEIPs ANSEVAQWR and EALVSQLTR were identified from T. lepturus myosin. The ACE inhibitory activity of ANSEVAQWR was stronger than EALVSQLTR. The mechanism of ACE inhibitory activity analysed by molecular docking was proposed. The binding strength in the model was further verified with SPR.